2017
DOI: 10.1002/mp.12051
|View full text |Cite
|
Sign up to set email alerts
|

A feasibility study of a deuterium–deuterium neutron generator‐based boron neutron capture therapy system for treatment of brain tumors

Abstract: Results demonstrated that a DD-based BNCT system could be designed to produce neutron beams that have acceptable in-air and in-phantom characteristics. The parameter values were comparable to those of existing BNCT facilities. Continuing efforts are ongoing to improve the DD neutron yield.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Neutron Generators (NG) are extensively used in the various industrial applications such as neutron radiography [1,2], neutron activation analysis [3][4][5], boron neutron capture therapy [6][7][8], explosive material detection [9,10] and material testing [11].…”
Section: Introductionmentioning
confidence: 99%
“…Neutron Generators (NG) are extensively used in the various industrial applications such as neutron radiography [1,2], neutron activation analysis [3][4][5], boron neutron capture therapy [6][7][8], explosive material detection [9,10] and material testing [11].…”
Section: Introductionmentioning
confidence: 99%
“…It was found that the weighted dose rate of brain tumors at a depth of 6.75 cm was 0.022 Gy(w)/s [21]. In 2017, Hsieh et al, used BSA design based on a DD neutron generator to show that the weighted dose rate of brain tumors at a depth of 3 cm is 0.0196 Gy(w)/s [22]. This study aims to calculate BNCT dosimetry in different of cancer positions and irradiation geometries using the PHITS code.…”
Section: Introductionmentioning
confidence: 99%